Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Zhang, Mo; Gao, Xiaolong; Lyu, Mingxin; Lin, Shihui; Su, Ying; Luo, Xuan; You, Weiwei; Ke, Caihuan (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai, attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai. Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.